Median Lethal Concentration of Zanthoxylum rhetsa seed extracts on Grass carp Fingerlings (Ctenopharyngodon idella) (Valenciennes, 1844) in Captive Condition - Jomang, Olik; Behera, S.; Bhakta, Dibakar; Baksi, Snigdha; Saha, Shibam (Fishery Technology, 2020)
The bark extracts of the plant Zanthoxylum rhetsa have been widely used by people of Arunachal Pradesh as a mean of catching fish. Therefore, the median lethal concentration (LC50) value of Zanthoxylum rhetsa bark extracts on grass carp (Ctenopharyngodon idella) (Valenciennes, 1844) has been determined in the present study. The seeds of Z. rhetsa were collected from the forest of Tarak village, located in the Siang district of Arunachal Pradesh and the toxicity test was conducted in the control condition. Five different concentrations of the extract viz., 25 mg l-1, 35 mg l-1, 45 mg l-1, 55 mg l-1 and 65 mg l-1 were prepared by adding the extracts proportionately to the water. The LC50 value of Z. rhetsa against C. idella was hosted as 45 mg l-1 for 96 h exposure period. Toxicity of aqueous solution of Z. rhetsa against fingerlings of grass carp was found to be time and dose-dependent. It was found that there was a significant (p<0.05) relationship between the mortality of the treated fish with the concentration of seed extract of Z. rhetsa. A very strong correlation coefficient was found between the mortality of test fish and exposure of seed extract of Z. rhetsa (r=0.998) at different concentrations. The finding established that Z. rhesta has a potential piscicidal effect on fish and could be used widely to control unwanted fishes in aquaculture systems.